2010
DOI: 10.1364/oe.18.018968
|View full text |Cite
|
Sign up to set email alerts
|

A composite microcavity of diamond nanopillar and deformed silica microsphere with enhanced evanescent decay length

Abstract: We report the experimental realization of a composite microcavity system, in which negatively-charged nitrogen vacancy (NV) centers in diamond nanopillars couple evanescently to whispering-gallery modes (WGMs) in a deformed, non-axisymmetric silica microsphere. We show that the deformed microsphere can feature an evanescent decay length four times larger than that of a regular silica microsphere. With the enhanced evanescent coupling, WGMs can in principle couple to NV centers that are 100 to 200 nm beneath th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…2). Detailed experimental studies have shown that evanescent decay length in regions 45 o away from a symmetry axis is of order 400 nm (with λ=800 nm), which is nearly 4 times of the evanescent decay length of conventional silica WGM resonators with no deformation [2]. For the deformed silica resonator, the WGMs can couple efficiently to NV centers within 200 nm of the diamond surface.…”
Section: Results and Discussion A) Enhancement Of Evanescent Decay Lmentioning
confidence: 99%
“…2). Detailed experimental studies have shown that evanescent decay length in regions 45 o away from a symmetry axis is of order 400 nm (with λ=800 nm), which is nearly 4 times of the evanescent decay length of conventional silica WGM resonators with no deformation [2]. For the deformed silica resonator, the WGMs can couple efficiently to NV centers within 200 nm of the diamond surface.…”
Section: Results and Discussion A) Enhancement Of Evanescent Decay Lmentioning
confidence: 99%
“…Furthermore, the free‐space coupling can avoid extra coupling loss, desirable for nonlinear processes and biochemical sensing experiments . Thirdly, the evanescent field can be enhanced in the deformed microcavities , and thus boost the light–matter interactions. Combining these advantages, there are many application benefits from this type of microcavities, including nanoparticle location detection , rotation‐speed sensing as well as optical energy storage .…”
Section: Applicationsmentioning
confidence: 99%
“…), including not only the smooth deformations of a circle or sphere and cavities with boundary defects, but also a vertical emission cavity with diffraction grating along the cavity circumference. Furthermore, several of the latest photonics applications of a WGM cavity with unidirectional emission are introduced, including wide‐band laser illumination source speckle‐free full‐field imaging , free‐space excitation , evanescent‐field enhancement , optical energy storage , and sensing .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many theoretical and experimental works have been devoted to the hybrid system in which NV centers are coupled with whispering-gallery-mode (WGM) microresonators. By using microspheres [25,26] and diamond-GaP microdisks [27], strong coupling between the NV center and WGM resonator has been experimentally realized. Wei and Deng [28] presented an efficient protocol for constructing two-qubit and threequbit quantum logic gates, including the CNOT gate, Toffoli gate, and Fredkin gate, acting on NV centers confined in microcavities.…”
Section: Introductionmentioning
confidence: 99%